Alternative Education Programs for High School Age Students in Chile. Issue 4 (May 2020) - Espinoza, Oscar; González, Luis; McGinn, Noel; Castillo, Dante
The provision of "alternative" education is increasingly common in the countries of the world, but highly varied in its forms and coverage. In its commitment to provide education for all to age 18, Chile recently expanded its system of schools for teenage dropouts and has funded research on how best to educate these youth. This article, based on data from a national sample of 18 recently established Second Opportunity Centers, describes student characteristics, their ambitions for their education and future, and their evaluation of their experience to date. Using a review of principally North American research findings as a guide, the study analyzes factors linked with grade repetition and withdrawal from school to suggest strategies that may be effective in increasing retention of students. This article concludes that, given multiple causes of school failure, reintegration into the education system requires multiple strategies.